Environmental Engagement, Religion and Spirituality in the Context of Secularization - Marie Briguglio; Teresa García-Mu\~noz; Shoshana Neuman (Institute of Labor Economics (IZA), 2020)
Over the past half century, a literature has developed across a range of disciplines exploring the relationship between religion and environmental engagement, including pro-environmental attitudes and behaviours.Empirical results are diverse and the relationship seems to vary in size and direction, depending on definitions and the method of investigation adopted. An increasingly important phenomenon which has received far less attention is that of spirituality, within/out the context of a religion. This paper contributes to the literature by examining the question in a predominantly Roman Catholic European Union country where church attendance is in decline. It employs a nationally representative dataset (n=1,029) which includes diverse measures of religiosity and spirituality, as well as measures of interest in environmental issues, in wildlife and natural history, and engagement in countryside activities and gardening, together with relevant socio-economic control variables. Our findings confirm that the usual socio-economic determinants are associated with this type of environmental engagement. We find that church attendance adds no further explanatory power to environmental engagement. On the other hand, participation in socio-cultural religious activities and self-assessed spirituality are positively and significantly associated of various dimensions of environmental engagement.
Keywords: O13; P18; Q51; Z12; 330; religion; spirituality; environment; catholic; secularization; quantitative